T-cell-receptor gene usage of Actinobacillus actinomycetemcomitans-reactive periodontal CD4+ T cells from localized juvenile periodontitis patients and human peripheral blood leukocyte-reconstituted NOD/SCID mice - Gao, Xuijuan; Teng, Yen-Tung A. (Journal of periodontal research, 2002)
We investigated the variable Vα and Vβ gene usage of Actinobacillus actinomycetemcomitans‐reactive periodontal CD4+ T cell receptors (TCR) from: (i) four A. actinomycetemcomitans‐infected localized juvenile periodontitis (LJP) patients, (ii) four groups of A. actinomycetemcomitans‐inoculated NOD/SCID mice engrafted with individual LJP‐derived HuPBL and (iii) HuPBL samples of four LJP patients and two healthy control subjects, by quantitative PCR analyses. The results show that: (i) the majority of the TCR genes (82.5% of Vα and 91.1% of Vβ) used by periodontal CD4+ T cells in A. actinomycetemcomitans‐inoculated HuPBL‐engrafted NOD/SCID mice overlap with those used by local periodontal T cells in LJP patients, (ii) although A. actinomycetemcomitans‐reactive periodontal CD4+ TCR repertoire is relatively widespread, there are a few dominant genes shared by the LJP patients, suggesting a limited number of antigens or epitopes commonly recognized and (iii) A. actinomycetemcomitans likely lacks superantigenic characteristics. These results suggest A. actinomycetemcomitans‐associated human CD4+ T cell repertoire established in HuPBL‐NOD/SCID mice provides a useful approach to study specific aspects of immune–parasite interactions in the periodontium.